METODE RASULULLAH DALAM MENDIDIK ANAK DAN KAJIAN TERHADAP HADIS TENTANG PERINTAH MENDIRIKAN SHALAT - Afendi, Achmad Ruslan; Ramli, Akhmad; Sudadi, Sudadi; Anwar, Chairul (Fakultas Ushuluddin, Adab, dan Dakwah UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Children are a brilliant age or the age at which children are currently able to digest all the information usually obtained from the general environment, and early childhood is also known as the golden age. At this age, children's habituation in strict quality development must be carried out consistently, which will be the tendency of children later into adulthood. Children are a gift and a mandate entrusted by Allah SWT to His servants who will be held accountable by Allah SWT in the hereafter. This paper aims to make parents aware of their role in educating children in teaching prayer. The study in this paper uses the Library Research method. The result of this study is that the family is the most important place where children can get their first education. The child's personality and character are first formed in the family environment, parents should have a concept in educating children, namely Religious and Moral Education. Which is the teaching of prayer that refers to the hadith of the Prophet Muhammad.